Characterizing Differences in Functional Connectivity Between Posterior Cortical Atrophy and Semantic Dementia by Seed-Based Approach - Chen, Yi; Zeng, Qingze; Wang, Yunyun; Luo, Xiao; Sun, Yan; Zhang, Lumi; Liu, Xiaoyan; Li, Kaicheng; Zhang, Minming; Peng, Guoping (Frontiers in Aging Neuroscience, 2022)
Background Posterior cortical atrophy (PCA) and semantic dementia (SD) were considered to be focal syndromes involving different cerebral regions. This study aimed to elaborate on the consequence of a localized damage on the functional connectivity with an affected network in posterior cortical atrophy (PCA), semantic dementia (SD) and cognitively unimpaired controls. Methods 10 PCA patients, 12 SD patients and 11 controls were recruited to undergo a detailed clinical history interview and physical examination, neuropsychological assessments, and PET/MRI scan. Seed-based functional connectivity (FC) analyses were conducted using regions of interest in the left anterior temporal lobe and superior temporal gyrus in language network, bilateral V1 region in visual network, and bilateral anterior insula in salience network, and further related the FC intensity to cognition. Meanwhile, the uptake value of fluorodeoxyglucose in regions with FC alteration to seeds was also extracted to compare. Results We found a global cognitive impaired in PCA and SD patients. The results of FC analyses showed that PCA patients present decreased FC in left precentral gyrus and increased right inferior frontal gyrus to seeds in visual network, right medial frontal gyrus and left fusiform to seeds in the language network, left superior temporal gyrus to seed in salience network, which were positively and negatively related to cognitive function respectively. SD patients had increased FC from right superior temporal gyrus, right middle frontal gyrus and right superior frontal gyrus to seeds in the language network, as well as right insula and left anterior cingulum to seeds in the salience network, negatively relating to cognitive function; but decreased FC in right superior frontal gyrus to seeds in the language network, and left superior frontal gyrus to seed in the salience network, positively relating to cognitive function. Most of the regions with FC change in PCA and SD patients had abnormal metabolism simultaneously. Conclusion Abnormal connectivity spread over the cortex involving language and salience network were common in PCA and SD patients, which also matched the observation that they showed several cognitive deficits, while FC change involving in visual network was unique to PCA patients.